Channel Islands Surnames of French Origin in North America. (2nd January 2017) - Picard, Marc
Abstract : Throughout the 18th and 19th centuries, migrants from the Channel Islands settled in various parts of North America. Many of them bore French names which their ancestors had brought over from Normandy and Brittany to Jersey and Guernsey in previous centuries. However, since many of these surnames were no longer found to exist in France or had evolved beyond recognition, their etymologies became irretrievable in standard French onomastic works. In this study, it will be shown that their origins can be ascertained for the most part by supplementing traditional research methods with the vast onomastic, geographical and genealogical data that has become available on the internet in recent years.